Range-based argumentation semantics as two-valued models - OSORIO, MAURICIO; NIEVES, JUAN CARLOS (Theory and practice of logic programming, 2017)
Characterizations of semi-stable and stage extensions in terms of two-valued logical models are presented. To this end, the so-called GL-supported and GL-stage models are defined. These two classes of logical models are logic programming counterparts of the notion of range which is an established concept in argumentation semantics.